Low-cost, high-precision integral 3D photography and holographic 3D display for real-world scenes - Sun, Zehao; Liu, Minghao; Dong, Jiaqing; Li, Zilong; Liu, Xuelin; Xiong, Jianghao; Wang, Yiguang; Cao, Yubin; Li, Jiahong; Xia, Zizhun; Liu, Qiegen; Song, Xianlin (Optics communications, 2024)
The lack of three-dimensional (3D) information limits the popularization and development of holographic technology. This paper proposes a low-cost, high-precision integral 3D real scene photography and holographic 3D display system using active fringe projection. The system solely relies on a projector, a CCD camera, and a computer to swiftly and accurately acquire 3D information (accuracy within 2 mm) through Fringe Projection Profilometry. Then, significantly effective 3D holographic reconstruction is achieved using a layer-based algorithm. Finally, the energy of image gradient operator is used to calculate the focus measurement of the image, and the change of the focus region is quantitatively analyzed. The performance of the system was tested using a box, and the experiment results were consistent with the simulation results, verifying the feasibility of the system. This method will further expand the application of holographic technology in medicine, the military, navigation, and other fields. 3D holographic display has been widely used in education, medical science, military and other fields, and has a very promising prospect of application. At present, the methods of the acquisition of 3D content used for 3D holographic reconstruction has the problems of high system complexity, high cost and low precision. To address this issue, this work proposed a low-cost, high-precision 3D real scene photography and holographic 3D display system using active fringe projection. The system solely relies on a projector, a CCD camera, and a computer to swiftly and accurately acquire 3D information (accuracy within 2 mm) through Fringe Projection Profilometry. Then, significantly effective 3D holographic reconstruction is achieved using a layer-based algorithm. Finally, the energy of image gradient operator is used to calculate the focus measurement of the image, and the change of the focus region is quantitatively analyzed. The performance of the system was tested using a box, and the experiment results were consistent with the simulation results, verifying the feasibility of the system. Compared with other methods, this method is simple, low-cost and high-precision (depth measurement accuracy within 2 mm). This work will further expand the application of 3D holographic display in the field of medicine, the military, navigation, industrial applications (industrial inspection, head-mounted displays etc.) and other fields.